Distribution, determination method, risk assessment, and strategy of exogenous pyrrolizidine alkaloids in tea - Ke Zan; Zhao Wang; Ying Wang; Jian-Dong Yu; Hong-Yu Jin; Shuang-Cheng Ma (Pharmacological Research - Modern Chinese Medicine, 2023)
Background and aim: Pyrrolizidine alkaloids (PAs) are secondary metabolites produced by plants. At present, more than 660 PAs have been identified in more than 6000 plants, mainly belonging to the families Boraginaceae, Compositae, Leguminosae, and so forth. PAs and their corresponding nitrogen oxides have variedtoxicities, including hepatotoxicity, pulmonary toxicity, and genotoxicity. The long-term intake of PAs can lead to cancer. This study aimed to review the literature on tea derived from C. sinensis only. Results: Tea is one of the most frequently items usedas both medicine and food. In recent years, PAs have been frequently detected in tea. The tea plant itself does not produce PAs, theymainly come from soil contamination caused by weeds in the tea garden. Conclusions: This study reviewed data published in recent years on the distribution, detection, risk assessment, strategy, and prospects of PAs in tea. The findings of this study mightfacilitate the qualityimprovementand safe use of PAs in tea.